2002
DOI: 10.1088/0953-8984/14/43/313
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure and phase transitions of the magnetic shape memory compound Ni2MnGa

Abstract: High resolution neutron powder diffraction and single crystal measurements on the ferromagnetic shape memory compound Ni 2 MnGa have been carried out. They enabled the sequence of transformations which take place when the unstressed, stoichiometric compound is cooled from 400 to 20 K to be established. For the first time the crystallographic structure of each of the phases which occur has been determined. At 400 K the compound has the cubic L2 1 structure, and orders ferromagnetically at T C ≈ 365 K. On coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
290
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(318 citation statements)
references
References 14 publications
26
290
1
1
Order By: Relevance
“…34 Atomic positions have not yet been determined for the monoclinic structure. Under such circumstances, our work is important because it shows that a new FSMA material can be predicted by computing the energy cost of formation of the martensitic phase in a simpler tetragonal structure.…”
Section: Discussionmentioning
confidence: 99%
“…34 Atomic positions have not yet been determined for the monoclinic structure. Under such circumstances, our work is important because it shows that a new FSMA material can be predicted by computing the energy cost of formation of the martensitic phase in a simpler tetragonal structure.…”
Section: Discussionmentioning
confidence: 99%
“…9 Mn 28.6 Ga 21.5 microwires, Qian et al reported that SIMT stress increased linearly with the temperature and could be described by Clausius-Clapeyron relationship 4 . The application of ternary Ni 2 MnGa SMAs is limited because of their low martensitic transformation temperature and high intergranular fracture tendency 5 . Thus, various options such as a fourth element doping and grain refinement have been used to improve the properties of Ni-Mn-Ga alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure at high temperature is the cubic L2 1 and transforms into a modulated tetragonal state at low temperature [1,2]. An important feature of the NiMn-Ga alloys is the occurrence of differently modulated intermediate structures that are observed in-between the initial and the final phase with the variation of temperature [3].…”
Section: Introductionmentioning
confidence: 99%